POLYAâ€™S STRATEGY: AN ANALYSIS OF MATHEMATICAL PROBLEM SOLVING DIFFICULTY IN 5TH GRADE ELEMENTARY SCHOOL - Nurkaeti, Nunuy (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2018)
Abstract:. Problem solving is one of ways to develop higher order thinking skills. Strategy of problem solving that can be developed in mathematics learning is Polya's strategy. This study aims to analyze the problem solving difficulties of elementary school students based on Polya strategy. To support this research,descriptive analysis is used on seven elementary school students . The results show that, the difficulty of mathematical problems solving of elementary school students consist of the difficulty of understanding the problem, determining the mathematical formula/concepts that is used, making connections between mathematical concepts, and reviewing the correctness of answers with questions. These happened because the problem presented is in a story problem, that is rarely studied by the students. Students usually solve mathematical problems in a form of routine questions, which only require answers in a form of algorithmic calculations.Â Abstrak: Pemecahan masalah adalah salah satu cara dalam mengembangkan kemampuan berpikir tingkat tinggi. Salah satu strategi pemecahan masalah yang dapat dikembangkan pada pembelajaran matematik adalah strategi Polya. Penelitian ini bertujuan menganalisis kesulitan pemecahan masalah siswa sekolah dasar berdasarkan strategi Polya. Untuk mendukung penelitian ini digunakan analisis deskriptif pada tujuh orang siswa sekolah dasar. Hasilnya menunjukkan bahwa, kesulitan pemecahan masalah matematik siswa sekolah dasar meliputi, kesulitan memahami masalah, menentukan rumus/konsep matematik yang digunakan, membuat koneksi antar konsep matematika, dan melihat kembali kebenaran jawaban dengan soal. Hal tersebut disebabkan, masalah yang disajikan berupa soal cerita yang jarang dipelajari siswa. Siswa biasanya menyelesaikan masalah matematik berupa soal rutin, yang hanya menuntut jawaban berupa perhitungan algoritmik.